Tunable Magnetic Antiskyrmion Size and Helical Period from Nanometers to Micrometers in a D2d Heusler Compound - Ma, Tianping; Sharma, Ankit K.; Saha, Rana; Srivastava, Abhay K.; Werner, Peter; Vir, Praveen; Kumar, Vivek; Felser, Claudia; Parkin, Stuart S. P. (Advanced Materials, 2020)
Skyrmions and antiskyrmions are magnetic nano-objects with distinct chiral, noncollinear spin textures that are found in various magnetic systems with crystal symmetries that give rise to specific Dzyaloshinskii–Moriya exchange vectors. These magnetic nano-objects are associated with closely related helical spin textures that can form in the same material. The skyrmion size and the period of the helix are generally considered as being determined, in large part, by the ratio of the magnitude of the Heisenberg to that of the Dzyaloshinskii–Moriya exchange interaction. In this work, it is shown by real-space magnetic imaging that the helix period λ and the size of the antiskyrmion daSk in the D2d compound Mn1.4PtSn can be systematically tuned by more than an order of magnitude from ≈100 nm to more than 1.1 µm by varying the thickness of the lamella in which they are observed. The chiral spin texture is verified to be preserved even up to micrometer-thick layers. This extreme size tunability is shown to arise from long-range magnetodipolar interactions, which typically play a much less important role for B20 skyrmions. This tunability in size makes antiskyrmions very attractive for technological applications.
CRIS-Team Scopus Importer:2022-04-14
Keywords: antiskyrmion; D; Heusler compound; Lorentz transmission electron microscopy; spintronics